Innovation in Fiqh Learning through the Implementation of Student Worksheets in Elementary Madrasahs - Fajriah Inayati; Ghina Fadlilah Sukmara; Figo Prilianto; Melinda Koestanti (Jurnal Iman dan Spiritualitas, 2026)
This study aims to analyze the implementation of Student Worksheets (LKPD) in Fiqh learning at Al Huda Private Elementary School (MIS), Haurwangi, Cianjur, West Java, as an effort to overcome conventional teaching methods and limitations of learning media. The study used a qualitative case study design. Data were collected through observation, interviews, and documentation, then analyzed using thematic analysis techniques. The results of the study indicate that the use of structured LKPD can transform Fiqh learning into a more interactive, contextual, and student-centered one, so that students' conceptual understanding and practical skills significantly improve. The implications of this study confirm that LKPD can be an effective, innovative learning medium to bridge the gap between theory and practice in students' daily lives. The originality of this study lies in its focus on practical innovations in Fiqh learning at the elementary school level, while also providing a reference model for educators in designing more engaging and effective teaching materials.